Artificial Feeds Given in Different Dose to the Growth and Feed Consumption of Semah Fish Seed (Tor Douronensis) in Order to Domestication - Sunarto, .; Sabariah, . (Jurnal Akuakultur Indonesia, 2009)
Semah fish (Tor douronensis) is a kind of freshwater fish pertained as a wild fish that almost extint and rare, therefore, it is necessary to preserve through the culture activity. Meanwhile, in fish culture effort, feed is considers as an important factor.  Thus, feed must meet a proper quality and quantity due to the fish maintenance, growth, and reproduction requirement. Test feed employed in this research was an artificial feed in form of pellet which was consists of 40% protein by dose tested of 3%, 6%, 9% and 12% of biomass weight. The result indicated that daily growth rate was ranged between 1.44-1.99% by highest growth achieved at feed dose 6% and from the quadratic regression analysis achieved optimal dose by 6.18%.  Daily feed comsumption rate of semah fish seed was ranged between 2.69-10.19% per day.  Feed efficiency was ranged between 13.85-54.09%, and survival rate was 100%. Keywords: dose, growth, feed comsumption, semah fish, Tor douronensis   ABSTRAK Ikan semah (Tor douronensis) adalah jenis ikan air tawar yang tergolong jenis ikan liar yang hampir punah dan sudah langka, karena itu perlu upaya pelestariannya dengan usaha pembudidayaan. Dalam usaha budidaya ikan, pakan merupakan salah satu faktor penting. Oleh sebab itu pakan harus berkualitas dengan kuantitas yang tepat sesuai dengan kebutuhan ikan untuk pertumbuhannya, pemeliharaan tubuh dan reproduksi. Pakan uji yang digunakan dalam penelitian ini adalah pakan buatan berupa pelet yang mengandung  protein 40% dengan dosis pakan yang diuji 3%, 6%, 9% dan 12% dari bobot biomassa. Hasil menunjukkan laju pertumbuhan harian berkisar antara 1,99-1,44% dengan pertumbuhan tertinggi dicapai pada dosis pakan 6% dan dari analisis regresi kwadratik diperoleh dosis optimum sebesar 6,18%. Laju konsumsi harian benih ikan semah selama penelitian ini berkisar antara 2,69-10,19 %/hari. Efesiensi pakan berkisar antara 54,09-13,85%, dan tingkat kelangsungan hidup 100% Kata kunci: dosis, pertumbuhan, konsumsi pakan, ikan semah, Tor douronensis